MENYOAL REGULASI PILKADA: UPAYA PENGUATAN KPU SEBAGAI PENYELENGGARA PEMILU - Dian Aulia (The Politics : Jurnal Magister Ilmu Politik Universitas Hasanuddin, 2016)
The General Election Commission, as election management body in Indonesia, has prepared regulations regarding the local elections. Unfortunately, despite its regulatory function, the General Election Commission has not had independent authority to formulate the General Election Commission Regulation. In the drafting process of the General Election Commission Regulation, the General Election Commission is obliged to consultate with the Indonesia’s House of Representative, including ten regulations related to local election that have been adopted. Whereas in this process, the obligation possibly could be used by the House of Representative’s members, which comes from political party, to insert their invidiual or party interests, in the regulations that have been drafted. In das Sollen, the House of Representative is expected to be a ”legislative advise” to the General Election Commission, that formulate the regulation. However, in das Sein, the role of the House of Representative shifts into a “legislative review”. This harms the independency of the General Commission Election as an independent election management body, including their authority to formulate election regulation. The research will use normative approach, which will be written in descriptive analysis method,this reseach will deeply analyze about how the General Election Commission Regulation, related to local election is formulated, in order to strengthen the General Election Commission’s power and bargaining position as national, independent, and permanent election management body.